Rereading the sacred view of Ardabili in committing murder with new dawns - somaiyeh aliakbary; mohammad hasan haeri; hossein naseri moghaddam (پژوهش‌های فقهی مسائل مستحدثه)
Sahar is one of the phenomena that has been discussed in all historical periods and has come to the fore in different ways during the passage of time and the change of human societies. Sahar, which is forbidden from the perspective of Islam, except in some cases, by seizing people, objects or affairs, causes It becomes an extraordinary act; In all ages, especially in the current age, magicians use new methods of magic, including black magic, some degrees of hypnosis, some computer games, etc., to have effects on people's minds and psyches, which sometimes take people's lives. Therefore, this basic question is raised: Is it possible for a sorcerer to take someone's life and kill him with his magic? If possible, what is the way to prove such a murder and what is the punishment for the perpetrator? Based on this, the present research with descriptive and analytical method in the opinion of the jurists has reached the conclusion that famous jurists, while accepting the reality of witchcraft, consider the occurrence of murder by witchcraft as possible, And the proof of such a murder is accepted by the confession of a sorcerer, and the punishment for the perpetrator is considered revenge or ransom depending on the type of murder; But from the famous point of view, proving such a murder with eyewitness testimony on this matter is not accepted, while the saint of Ardabili considers it possible to prove murder by witchcraft with eyewitness testimony and accepts this testimony. Of course, those who believe that there is no magic, have not accepted the possibility of murder by magic, but with the sorcerer's confession of such a murder, they have considered killing the sorcerer for the purpose of Hadad.